The Effects of Problem-Based Learning on Critical Thinking, Motivation, and Learning Outcomes in Indonesia: A Systematic Review - Indriyani, Heni Kartika; Purwaningsih, Dyah; Khaokhajorn, Wacharaporn (FKIP Universitas Lampung, 2025)
The Effects of Problem-Based Learning on Critical Thinking, Motivation, and Learning Outcomes in Indonesia: A Systematic Review. Objective: This study systematically examines the implementation of Problem-Based Learning (PBL) in teaching the reaction rate topic in Indonesia. It covers research methods, measured variables, implementation strategies, and media, as well as the effects of PBL on students' critical thinking, motivation, and learning outcomes. Methods: A systematic literature review was conducted following the PRISMA framework (identification, screening, eligibility, and inclusion) to ensure rigorous and transparent article selection. Articles published between 2015 to 2025 were retrieved using the Publish or Perish tool from Scopus and Google Scholar, resulting in 24 articles. Data were analyzed using Thematic synthesis based on Braun and Clarke’s framework: (1) familiarization involved repeated reading of articles to understand content; (2) initial coding assigned meaningful labels to key data; (3) searching for themes grouped related codes; (4) reviewing themes refined coherence and relevance; (5) defining and naming themes clarified scope and meaning of each theme; (6) a coherent narrative synthesis integrated findings to highlight patterns and research gap. Results: The Use of PBL with students’ worksheets (9 articles) proved to be the most effective in enhancing students’ critical thinking, motivation, and learning outcomes in Indonesia. Research is dominantly quantitative (22 articles, 91.67%), with R&D limited (2 articles, 8.33%), indicating a need for more mixed-methods and qualitative research. A total of 12 articles (50%) investigated critical thinking, six articles (25%) focused on motivation, and 15 articles (63%) measured learning outcomes. No study simultaneously measured critical thinking and motivation, highlighting a research gap. Use of other media remains limited. Conclusion: Using PBL with students’ worksheets and other instructional media effectively improves students’ critical thinking, motivation, and learning outcomes on the reaction rate topic in Indonesia and guides the development of technology-integrated strategies, while encouraging future research on diverse methodologies and simultaneous measurement of cognitive and affective outcomes. Keywords: critical thinking skills, learning motivation, learning outcomes, problem-based learning, reaction rate.